Nitrate derived from beet juice and its influences on high-intensity exercise: a systematic review of randomized clinical trials - Guerra, Camila Venancia; Soares, Barbara E. Silva; Oliveira Morais, Fellipe Mateus A. de; Porto, Andrey Alves [UNESP]; Benjamim, Cicero Jonas R. (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2022)
Nitrate (NO3) supplementation through beetroot juice seems effective in high-intensity and short-duration exercises, which primarily use the anaerobic metabolic pathway. In order to clarify these issues, a systematic review was developed to investigate the effects of the use of NO3 supplementation derived from sugar beet on performance. The search was performed in PubMed (via MedLine), Cochrane Library, and EMBASE using the search strategy: Athletic Performances OR Sports OR Performance AND Nitrates OR Beta vulgaris OR Beet. The primary study population should include healthy, physically active adults aged 18 to 65 years. The intervention with NO3- should be beetroot juice and controlled with placebo intervention, with characteristics similar to beetroot juice and depleted in NO3. The studies should bring as outcome variables of physical performance in exercises with a predominantly anaerobic metabolic pathway. We consider single or double-blind, randomized clinical trials. 177 articles were found in the databases, which after the screening and eligibility stages, only 9 remained in the sample. The intervention with NO3 from beet juice showed essential contributions in the performance tests of the primary studies. Most of the included trials showed better results in the group that ingested NO3. It can conclude that NO3 from beetroot juice is an essential ergogenic resource in high intensity and short duration activities, and, therefore, it can be used in conditions that aim to increase the performance of athletes.
Keywords: Beta vulgaris L; Nitrate; Performance; Exercise; Sports